Rearticulating theory and methodology for perezhivanie and becoming: Tracing flat CHAT assemblages and embodied intensities - Prior, Paul; Hengst, Julie; Kovanen, Bruce; Mazuchelli, Larissa; Turnipseed, Nicole; Ware, Ryan (Outlines. Critical Practice Studies, 2024)
Taking up Lemke’s (2000) critical questions of how moments add up to lives and social life, we articulate theoretical and methodological frameworks for perezhivanie and becoming, challenging binaries that splinter entangled flows of perezhivanie into frozen categories. Working from a flat CHAT notion of assemblage to develop an ontology of moments, we stress consequentiality, arguing it emerges in intersections of embodied intensities (not only affective, but also indexical, intra-actional, and historic), the dispersed bio-cultural-historical weight of artifacts and practices, and dialogic resonances across moments. Methodologically, we take an ethico-onto-epistemological perspective to systematically study perezhivanie. The bio-ecological model of rich environments (centered around meaningful complexity, agency, and individual optimization) offers both a key framework for understanding becoming and a design framework for transdisciplinary realizations of ethico-onto-epistemological practice. We illustrate these frameworks with examples from four research projects: a university physics lab group doing and writing an experiment, a former pastor managing bipolar disorder and rejecting faith, a sustained social justice education program at a university, and intersections of aging policies, media representations, and stroke survival in Brazil. Finally, we argue that an ontology of moments centered on consequentiality can illuminate perezhivanie’s relationship to becoming and that the model of enriched environments offers metrics to assess and design environments.